BIM in Precast Construction: A Case Study of Highrise Residential Building - Yin Rui; Lim Yaik Wah (Journal of ICT, Design, Engineering and Technological Science, 2018)
The study objectives are to analyze BIM application in the project practice and evaluate different implementation influence during the construction period. Building Information Modelling (BIM) combines various building information data in the model. It has a series of characteristics of visualization, coordination, simulation, optimization, and others. For the whole life cycle of building, BIM has prominent advantages in project management and operation management. The main research method is the case study for this paper. The case Forest City project reported BIM application on a typical high-rise condominium project in Malaysia. Two precast residential buildings executed the BIM tool for construction management. The participants tried to use the entire construction process simulation. They intend to obtain the best management method to improve their work efficiency and reduce project cost. From the Forest City project case study, the designers and engineers provided various precast components 3D presentation. It reduced rework through BIM clash detection. Main-con QS took off this project quantity accurately through the BIM platform. BIM technology helped relevant participants to improve work efficiency. The research implications are displayed a useful technology for precast construction management, such as BIM 3D/4D/5D functions.